Unlocking playful dimensions: Developing and validating a scale for assessing video game-related hedonic experiences - Amir Zaib Abbasi; Ding Hooi Ting; Helmut Hlavacs; Bradley Wilson; Mousa Albashrawi; Yogesh K. Dwivedi (Journal of Innovation & Knowledge, 2025)
This study aims to develop and validate an instrument to measure video game-related playful consumption experiences (PCEs), assessing a player’s imaginal, emotional, and sensory experiences during video gameplay. We initially conceptualize the theoretical framework of video game-related PCEs. Next, we develop a scale through three analytical phases. In the first phase, exploratory factor analysis is conducted with 225 Malaysian video game players. In the second phase, the partial least squares structural equation modeling (PLS-SEM) is applied to a sample of 444 Malaysian gamers to validate the scale at a higher-order level and evaluate the conceptual model’s acceptability. In the third phase, the PCE scale’s nomological validity is established using the Theory of Reasoned Action (TRA) by analyzing 294 Pakistani PUBG players with the PLS-SEM approach. All hypotheses based on the TRA network are supported. This study uniquely applies the hedonic theory of consumption to operationalize PCEs, assessing gamers’ playful experiences. Additionally, it extends the TRA by elucidating attitude formation through PCEs in PUBG gameplay.